2016
DOI: 10.14400/jdc.2016.14.1.291
|View full text |Cite
|
Sign up to set email alerts
|

The convergent influence of Perceived Stress and the Empowerment on Rehabilitation motive of Stroke patients

Abstract: 주제어 : 스트레스, 임파워먼트, 재활, 동기, 뇌졸중, 환자, 융복합 Abstract The purpose of this study has been done to identify the influencing factors on rehabilitation motive of stroke patients. A sample of 138 stroke patients in Long-term Care and rehabilitation hospitals completed questionnaires through face -to -face interviews. Data were analyzed using descriptive statistics, t-test, ANOVA, Pearson's correlation coefficient, and Stepwise multiple regression. Rehabilitation motive of stroke pacients was correlated with empowerment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Hence, to improve stroke patients’ rehabilitation motivation, the focus should be on self-efficacy among the internal factors and psychological variables, and on social support among the external factors and environmental variables, while a therapeutic intervention should be developed to reduce the risk factors (financial burden, etc.). This was consistent with Kim et al [ 24 ], who suggested that self-efficacy , among the motivational factors, enabled people to produce continuous outcomes and participate in therapeutic immersion. Furthermore, support as an external factor [ 26 ] acts as an external resource.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, to improve stroke patients’ rehabilitation motivation, the focus should be on self-efficacy among the internal factors and psychological variables, and on social support among the external factors and environmental variables, while a therapeutic intervention should be developed to reduce the risk factors (financial burden, etc.). This was consistent with Kim et al [ 24 ], who suggested that self-efficacy , among the motivational factors, enabled people to produce continuous outcomes and participate in therapeutic immersion. Furthermore, support as an external factor [ 26 ] acts as an external resource.…”
Section: Discussionsupporting
confidence: 91%